Factors affecting the import of soybean in Indonesia - Adlaida Malik; Saidin Nainggolan (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2020)
As an agricultural country, Indonesia still imports soybeans to meet domestic soybean needs. The gap between national soybean production and consumption causes the government to import. Based on this, this study aims to analyze the factors that influence soybean imports in Indonesia. The data used are time series data for the period 2003-2018. Data is sourced from the Food and Agriculture Organization (FAO), United Nations International Trade Statistics Database (UN COMTRADE), the Central Bureau of Statistics of the Republic of Indonesia, World Bank, Bank Indonesia, and the Ministry of Trade of the Republic of Indonesia. The analysis method uses SEM-Partial Least Square (PLS). The results showed that the macroeconomic conditions directly affect soybean production and consumption. On the other hand, consumption has a direct effect, but production has no direct effect on soybean imports. Macroeconomic conditions do not have a direct effect on soybean imports. Nevertheless, the total effect (combined direct and indirect effects) is significant from macroeconomic conditions on soybean imports.